Exploring the Association between Levels of Police Presence, Contact, and Perceptions of Police Legitimacy - Bolaji, Qassim (Crime & delinquency, 2024)
Our goal was to investigate how increased police presence and contact are related to police-community relations, and whether this relationship may be different for those who are more likely to be subject to targeted policing practices, especially those with preexisting lower procedural justice assessments, living in disadvantaged communities, and having prior experience with the criminal justice system. Increased police presence was related to higher police legitimacy assessments, while low quality contact was negatively associated with police legitimacy. Increased presence and positive contact with the police were related to improved attitudes towards the police for those living in disadvantaged neighborhoods and who had preexisting lower procedural justice assessments. The opposite relationship was found for those living in advantaged neighborhoods with more positive preexisting attitudes towards the police. Implementation of tactics that increase police presence and positive contact with the police could improve police-community relations in neighborhoods that are disadvantaged and have residents that see the police as procedurally unjust.